Selecting the nomenclature of quality indicators of hybrophobized fur velour by expert method - Данилкович, Анатолій Григорович; Хлєбнікова, Наталія Борисівна; Омельченко, Наталія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2014)
The expenditure model of fur product, made of the hydrophobized fur velour, exploited at low temperatures, taking into account large dynamic loads, high humidity (rain, snow) was constructed. Scientific and regulatory documentation on existing nomenclatures of quality indicators of fur semi-finished products was analyzed. A common list of quality indicators of the fur velour was compiled. Questionnaires, instructions were developed, an expert group was formed. The survey was carried out, and results processing was performed using the author’s application program. Significance of quality parameters of the hydrophobized fur velour was defined. To assess the hydrophobized fur velour, the question of what properties new materials should be endowed with and what parameters determine their quality is relevant. Significance of indicators, characterizing the hydrophobized fur velour quality was determined. Nomenclature of these indicators included the total thermal resistance of fur skin, relative residual elongation of skin tissue at a stress of 4.9 MPa, color design of skin tissue and hair, water permeability of skin tissue in dynamic conditions, its relative elastic elongation at the stress of 4.9 MPa, vapor permeability, air permeability, tensile strength of skin tissue, decoration and relative total elongation of skin tissue at a stress of 4.9 MPa. For further research, in the process of ranking, three groups of indicators that characterize the functional (operational), aesthetic, ergonomic (hygiene) properties were selected, their significance was defined. For the consumer it is important that clothes, made of fur velour, which is exploited not only at low temperatures and dynamic loads, but also in conditions of specific precipitations such as rain, sometimes even snow, had proper moisture resistance. The nomenclature of indicators of consumer properties is sufficient for an objective assessment of complex quality indicator of hydrophobized fur velour, which is confirmed by the high concordance of opinions of specialists, who participated in the expert survey (concordance coefficient was 0.894).